1985
DOI: 10.1002/cne.902420203
|View full text |Cite
|
Sign up to set email alerts
|

Prosencephalic afferents to the mediodorsal thalamic nucleus

Abstract: The afferent projections from the prosencephalon to the mediodorsal thalamic nucleus (MD) were studied in the cat by use of the method of retrograde transport of horseradish peroxidase (HRP). Cortical and subcortical prosencephalic structures project bilaterally to the MD. The cortical afferents originate mainly in the ipsilateral prefrontal cortex. The premotor, prelimbic, anterior limbic, and insular agranular cortical areas are also origins of consistent projections to the MD. The motor cortex, insular gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

1987
1987
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(17 citation statements)
references
References 44 publications
1
14
0
2
Order By: Relevance
“…We previously reported that D projected to the rostral part of the reticular nucleus of the thalamus and had reciprocal connections with the zona incerta (Nakamura and Kawamura, 1988). The rostral part of the reticular nucleus of the thalamus forms a network with the intralaminar nuclei, the ventral frontal cortex, and the mediodorsal nucleus (Velayos and Reinoso-Suarez, 1985). The mediodorsal nucleus also has connections with medial, orbital, and dorsolateral prefrontal areas (GoldmanRakic and Porrino, 1985;Illinsky et al, 1985;Ray and Price 1993).…”
Section: Jh1972mentioning
confidence: 93%
“…We previously reported that D projected to the rostral part of the reticular nucleus of the thalamus and had reciprocal connections with the zona incerta (Nakamura and Kawamura, 1988). The rostral part of the reticular nucleus of the thalamus forms a network with the intralaminar nuclei, the ventral frontal cortex, and the mediodorsal nucleus (Velayos and Reinoso-Suarez, 1985). The mediodorsal nucleus also has connections with medial, orbital, and dorsolateral prefrontal areas (GoldmanRakic and Porrino, 1985;Illinsky et al, 1985;Ray and Price 1993).…”
Section: Jh1972mentioning
confidence: 93%
“…Here we emphasize that the thalamic input to the portion of area 46 surrounding the fundus of the anterior PS arises from a portion of lateral MD distinctly different from that forming connections with the portion of 46 at the outer edges of the caudal PS. These differences in the thalamic projections are likely to be associated with important functional differences, given the unique profiles of subcortical afferents associated with MDmc and MDpc (Harting et al, 1980;Porrino et al, 1981;Velayos and Reinoso-Suarez, 1982;Ilinsky et al, 1985;Velayos and Reinoso-Suarez, 1985;Russchen et al, 1987;Erickson et al, 2002).…”
Section: Lateral Divisions Of Md: Connections With Three Distinct Cormentioning
confidence: 93%
“…In some species, e.g., in the rhesus mon key, the cytoarchitectural heterogeneity is obvious, whereas in others, e.g., cats, rats and opossums, the cytoarchitecture is uni form throughout the nucleus [Akert, 1964;Benjamin and Golden, 1985;Krettek and Price, 1977;Velayos and Reinoso-Suarez, 1985].…”
Section: Discussionmentioning
confidence: 99%